2015
DOI: 10.1089/wound.2015.0628
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Friction on Skin at Risk: The Use of 3MCavilonNo Sting Barrier Film

Abstract: Objective: To compare the coefficient of friction (CoF) of skin against fabric when the skin is covered with a liquid barrier film versus a silicone dressing, relative to a bare skin baseline.Approach: A laboratory instrument allowing the measurement of friction between two surfaces was used to compare the CoF between a fabric representing bed linen (100% cotton) and the skin of two laboratory operators, either bare (dry or hydrated) or covered with a liquid barrier film or a silicone dressing.Results: The CoF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Barrier film provides a protective interface between skin and adhesive and helps reducing the friction coefficient; there is no need to remove this product, which may be reapplied as necessary. Clinical studies show that barrier films have the capacity of reducing erythema and skin flaking after removal of the adhesive material; its use in people at risk of developing cutaneous injury is therefore essential (2,(24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…Barrier film provides a protective interface between skin and adhesive and helps reducing the friction coefficient; there is no need to remove this product, which may be reapplied as necessary. Clinical studies show that barrier films have the capacity of reducing erythema and skin flaking after removal of the adhesive material; its use in people at risk of developing cutaneous injury is therefore essential (2,(24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…The fore udder attachment of cows becomes looser with increasing age, which could lead to moving of the udder skin across the UCD lesion, so called friction. It has been shown that friction impedes the process of wound healing (Bernatchez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The results both corroborate and conflict with the results of the studies of dressing frictional and shear properties which used different interface materials and loading values. Call et al 3 and Bernatchez et al 13 based their testing on a surface drag standard 14 . Call et al used a ground steel contact material and a nondisclosed force on the dressings while Bernatchez et al used a fabric interface and loading over a 4‐25 N range.…”
Section: Discussionmentioning
confidence: 99%
“…The results both corroborate and conflict with the results of the studies of dressing frictional and shear properties which used different interface materials and loading values. Call et al 3 and Bernatchez et al 13 based their testing on a surface drag standard. 14 One hypothesis is that dressings alter the induced shear forces on the skin that contribute to a beneficial effect.…”
Section: Discussionmentioning
confidence: 99%